Interior Preferences in Home Workspace Based on Changes in Behavior and Needs to Sustain Professional Work Productivity - Lee , Song Yuan; Azmi, Athira (MAJ - Malaysia Architectural Journal, 2023)
Remote working grows at its own moderate pace and has only been picked up by little numbers of selected professionals since 1979. The World Health Organization (WHO) declared the outbreak a Public Health Emergency of International Concern on 30 January 2020, and a pandemic on 11 March 2020. Millions of people were furloughed or lost jobs, and others rapidly adjusted to working from home as offices closed. With this abrupt change (WFH) came the challenge of blurred lines between career and personal life. However, the changes in behavior and needs of the people in this remote working environment are uncertain and the interior preferences of home workspaces are less investigated. Therefore, this research will focus on investigating the interior preferences of home workspaces due to the professional workforces’ changes in behaviors and needs in the remote working environment to sustain equal productivity as in the office.